2015
DOI: 10.1177/2165079915607870
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Vanpooling to Work

Abstract: Shared commutes to work, such as vanpooling, benefit the environment and provide economic gain for riders in terms of fuel costs, parking fees, and personal vehicle wear and tear. Although ride sharing is commonly believed to promote health through stress reduction, published evidence on this topic is limited, and findings vary. This study explored the perceived health and well-being of vanpoolers using a qualitative, descriptive design. Five focus groups of vanpoolers and two individual interviews with driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We identified ten studies that examined the benefits of health promotion interventions on sleep. 22,24,25,27,[54][55][56][57][58][59] Two studies evaluated the effects of encouraging increased physical activity on sleep. Bouchard et al converted seated workstations into treadmill workstations in the office of nurses and dieticians who ordinarily sat at desks for much of the day.…”
Section: Health Promotion Interventionsmentioning
confidence: 99%
“…We identified ten studies that examined the benefits of health promotion interventions on sleep. 22,24,25,27,[54][55][56][57][58][59] Two studies evaluated the effects of encouraging increased physical activity on sleep. Bouchard et al converted seated workstations into treadmill workstations in the office of nurses and dieticians who ordinarily sat at desks for much of the day.…”
Section: Health Promotion Interventionsmentioning
confidence: 99%
“…Finally, not being able to travel limits opportunities for social interaction while travelling. This applies mostly to public transport trips (Green et al 2014), but improvement on interpersonal relationships has also been reported by individuals sharing cars/vans to go to work (Robbins et al 2015).…”
Section: Travel Constraints Vs Social Participationmentioning
confidence: 99%
“…Additionally, in 2015 a team of researchers at the University of California Los Angeles interviewed a selection of its vanpool participants to reveal their perceived benefits of using a vanpool. Based on respondent information from recorded statements, the study determined that ''riders indicated that participating in a vanpool was a source of dramatic reduction in stress'' (38). There is a multitude of studies that link commuting stress to manifestations of illness-based absences from work or diminished work performance; a broad review of the literature can be found in Novaco and Gonzalez (36).…”
Section: Health Impacts On the Travel Experiencementioning
confidence: 99%